Gods, false -Gods and the untouchables - "Biswas, Swapan Kumar" (Calcutta Orion, 1998)
When Mahatma Gandhi was working as a law yer in South Africa he grovelled before the Whites of South Africa pleading "Since the Britishers and Indians were from the same Aryan stock, how could the Britishers rule over their own blood-brothers?" It was unfair for one set of Aryans to rule over another set, Gandhi believed. So we have this great man pleading the cause of Indian Aryans and not Indians in general and yet entire India calls. him Father of the Nation! He fought for free dom, they say. Whose freedom? From Whom? During the haydays of British rule many "Na tionalist Gods" said that it (the British rule) was good and essential. Why? Because it was an essential prelude to the revival of Hindu ism" said one worthy. Whom was this revival going to serve? The sub-human wretched Dalits? When the 'freedom' fighters were busy struggling for freedom (Again, whose free dom? From whom?) Dr. Ambedkar was look ing up to the British to help the cause and upliftment of the Untouchables. That was the only mission of his life. It was He who was fighting for the real freedom. But now he is being vilified as a British lackey and an anti national (whatever that may mean). The opin ion-makers, intellectuals, super-patriots et al have begun to find faults with Ambedkar, Ambedkarites and even started ridiculing the Dalits. The psychology behind this is of course caste hatred. And the reason behind this ha tred is that the downtrodden, the dalits, the deprived have suddenly become powerful by gaining political as well as social voice due to the efforts of one single man, AND HIM ALONE. The Dalits have started demanding a fair share of what the upper castes had been enjoying since time immemorial and this has been causing much consternation in the minds
Keywords: Untouchables